Campesinato e agroecologia na Colômbia: um estudo sobre as práticas produtivas e a relação com a natureza dos camponeses da Associação de Apicultores do Maciço Colombiano - APIMACIZO - Cadena Bastidas, Diana Carolina (Universidade Federal de São Carlos, 2018)
The aim of this research is to analyze the model of appropriation of nature from the concept of Agroecology, in a group of peasants associated in the Association of Beekeepers of the Colombian Macizo -APIMACIZO-, located in the municipality of La Vega, department of Cauca, Colombia. The fieldwork was developed during the second semester of 2016 in the first semester of 2017, a period in which semi-structured interviews were carried out with questionnaires, which were applied to 41 members of the Association, as well as open interviews that served as an input to implement the oral history methodology. The text is organized into four chapters, whereby three (chapters, one, two, three) are articles of this research. Chapter one aimed to analyze the process of emergence and consolidation of apicultural activity in APIMACIZO, the methodology used was based on semi-structured interviews and oral history (in order to understand the dynamics of the group through time through the oral reports), as a result there was an articulation of different sectors in apicultural practice, as well as the vindication of the peasant-beekeeper identity in the region. Chapter two aimed to describe the organizational form of the members of APIMACIZO, as well as their family productive systems and labor relations in the region. For this, questionnaires were used among the peasants of the association, as a conclusion it was possible to show that the relationships of the agricultural work are based on principles of reciprocity and solidarity, which have been fundamental for the organization of this group. Chapter three aimed to analyze the production model made by the members of the Association, based on the theoretical framework of agroecology. Methodologically, a bibliographic review was first carried out on the concept of Agroecology in Colombia, as well as on public policies of sustainable rural development. Subsequently, data collected in the field was used to investigate the knowledge of the interviewees about agroecology. One of the most significant results was to verify that peasants of APIMACIZO have a great respect for nature by not abandoning their traditional productive practices (sowing with shade, short and medium rotation crops, species diversity and variety of native seeds) and labor relations, which are based on solidarity and reciprocity among family members and neighbors. These working relationships in rural production are the way the peasants of APIMACIZO articulate with nature, that is, they appropriate nature through work to make it a social element.
Peasantry and agroecology in Colombia: a study on productive practices and the relationship with nature of the peasant of the association of beekeepers of the Colombian Macizo-APIMACIZO
Keywords: Campesinato; Agroecologia; Colômbia; Produção Rural; Peasants; Agroecology; Rural development; CIENCIAS AGRARIAS